1981
DOI: 10.1016/0167-0115(81)90062-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of cholecystokinin-like peptides by a crude rat brain synaptosomal fraction: A study by high pressure liquid chromatography

Abstract: Degradation of CCK-8, CCK-4, and related peptides by a crude synaptosomal fraction of rat brain was investigated by monitoring the tryptophan fluorescence of reaction products after HPLC fractionation. At 20 degrees C, the half disappearance time was 52 min for CCK-8, 35 min for unsulphated CCK-8, 20 min for unsulphated CCK-7, 6 min for Tyr(SO3H)-Trp-Met-Asp-Phe-NH2, and 3 min only for CCK-4. Caerulein was much more resistant than CCK-8, and Boc-CCK-4 and Aoc-CCK-4 remained stable for at least 3 h. The apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 41 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Cholecystokinin octapeptide (CCK-8) and Phe-Met-Arg Phe (FMRF) amide were shown to be released by (3-end (33) and morphine (34), respectively; and the regional dis tribution of these anti-opiate peptides in the brain was in dicated to be different from that of Met-enk (35,36). It was reported that CCK-8 was inactivated exclusively by aminopeptidase and enkephalinase (37), and the degrada tion of CCK-8 was reduced by bacitracin (38,39) and bestatin + phosphoramidon (40). The release of the C-ter minal phenylalanylamide of FMRF amide was induced by enkephalinase, and this hydrolysis was completely inhibit ed by phosphoramidon (40).…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin octapeptide (CCK-8) and Phe-Met-Arg Phe (FMRF) amide were shown to be released by (3-end (33) and morphine (34), respectively; and the regional dis tribution of these anti-opiate peptides in the brain was in dicated to be different from that of Met-enk (35,36). It was reported that CCK-8 was inactivated exclusively by aminopeptidase and enkephalinase (37), and the degrada tion of CCK-8 was reduced by bacitracin (38,39) and bestatin + phosphoramidon (40). The release of the C-ter minal phenylalanylamide of FMRF amide was induced by enkephalinase, and this hydrolysis was completely inhibit ed by phosphoramidon (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ill-characterized acidic (13,14) or neutral aminopeptidases (13), enkephalinase (EC 3.4.24.11) (15)(16)(17), a thiol-endopeptidase (18) or a metallo-endopeptidase (19) may participate in the hydrolysis of exogenous by cerebral membranes, with cleavages occurring at various peptide bonds within the molecule. However, numerous peptidases capable of hydrolyzing neuropeptides are present in cerebral membranes, and metabolic pathways of exogenous neuropeptides may not reliably reflect those responsible for endogenous neuropeptide inactivation, as illustrated in the case of enkephalins' (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Both chelation of ions and blocking of sulfhydryl groups could inactivate enzymes involved in the biosynthesis and/or degradation of CCK and, thus, explain otir data. Recently, a CCK-8 and CCK-4 degrading enzyme was detected in both the cytosol and the synaptic membranes of brain tissue (33). Moreover, in vitro experiments showed that the degradation of CCK-8 and CCK-4 could be markedly inhibited by both chelating and sulfhydryl-blocking agents, suggesting that their degradation required the presence of a metal ion probably linked to a thiol group (33).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, a CCK-8 and CCK-4 degrading enzyme was detected in both the cytosol and the synaptic membranes of brain tissue (33). Moreover, in vitro experiments showed that the degradation of CCK-8 and CCK-4 could be markedly inhibited by both chelating and sulfhydryl-blocking agents, suggesting that their degradation required the presence of a metal ion probably linked to a thiol group (33). Our results could be explained by reversible inactivation of such a CCK degrading enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation